Pengaruh Strategi Fundraising Wakaf, Literasi Wakaf, dan Citra Lembaga terhadap Minat Berwakaf dengan Religiusitas sebagai Variabel Moderating (Studi Lembaga Wakaf Muhammadiyah Kabupaten Lamongan) - Ambar Ayuningsih; Qi Mangku Bahjatullah (Universitas Muhammadiyah Surabaya, 2023)
This research is to explain the relationship between waqf fundraising strategies, waqf literacy and institutional image. Apart from that, this research also explains the role of religiosity as a moderating variable which is expected to provide a detailed picture of the relationship between waqf fundraising strategies, waqf literacy and institutional image on interest in waqf. This research uses quantitative methods. Where the data source used is primary data obtained from questionnaires. In this research, the sampling technique used was convenience sampling. This sampling technique is based on chance alone, members of the population that the researcher meets and are willing to become respondents are used as samples. The sample in this research was 100 respondents. The results of this research show that: (1) The fundraising variable has a positive and significant influence on people's interest in giving waqf. (2) The literacy variable has a positive and significant effect on people's interest in giving waqf. (3) The institutional image variable does not have a positive and significant effect on people's interest in giving waqf. (4) The moderating variable, namely religiosity, cannot moderate fundraising on people's interest in waqf. (5) The moderating variable, namely religiosity, cannot moderate literacy on people's interest in giving waqf. (6) The moderating variable religiosity can moderate the image of the institution on people's interest in waqf.